Household Perception of Environmental Degradation and Its Impact in Rural Edo State, Nigeria - Igben, Jomata Lucky; Ihayere, Celestina Abamefeghe (Journal of Sustainability and Environmental Management, 2025)
This study assesses the perceived impact of environmental degradation on the population of Ovia North East Local Government Area (LGA) of Edo State, Nigeria. It aims to identify typologies and analyse the impacts of environmental degradation on rural populations. Data for the study were obtained from a structured questionnaire administered to a sample of 200 household heads, selected using a two-stage sampling design. The first stage involved a random selection of four from 10 settlements. The second stage was a systematic random sampling of 50 households in the selected settlements. The questionnaire covers socio-demographic characteristics of the respondents, typology and level of impact of environmental degradation. Data were analysed using descriptive statistics, namely frequency, percentage, and simple mean. In addition, the null hypothesis that there is no significant variation in the perceived level of impact/effects of environmental degradation on the population was tested using the Analysis of Variance (ANOVA). The study identified gas flaring, gully erosion, flooding, deforestation, water, air, and soil pollution as major forms of environmental degradation, resulting in the loss of fertile land, infrastructure, employment, aquatic life, and biodiversity, and increasing insecurity and poverty. There were no significant variations in the perceived impacts of environmental degradation (F = 8.19; 12.519, P<0.05) among the selected settlements. The study recommends conducting an environmental impact evaluation of the causes of degradation, in addition to educating the local population on the need for sustainable development.